PEMBERDAYAAN MASYARAKAT BERBASIS MANAJEMEN PERSAMPAHAN DAN PERMUKIMAN BERKELANJUTAN DI KELURAHAN LEATO UTARA KECAMATAN DUMBO RAYA KOTA GORONTALO - Koniyo, Yuniarti; Hippy, Mohammad Zubair; Gobel, Muhammad Rizq; Machieu, Siti Rahmatia (Universitas Mataram, 2024)
The province of Gorontalo has the potential for waste generation reaching 246,397.112 tons, primarily from households (48 percent), traditional markets (24 percent), and commercial areas (9 percent). Of the 140 tons of waste produced daily in Gorontalo City, only 70 tons are transported by the Environmental Services Department to the Talumelito Regional Landfill, while the remainder is left without adequate management, resulting in environmental damage. The community service program through the Community Service Learning (KKN) in Infrastructure aims to enhance sustainable waste management in Leato Village. Activities will involve KKN students in educating the community on environmentally friendly waste management practices, conducting Focus Group Discussions (FGDs), forming community self-help groups, mapping waste issues in the environment, and developing collaborative solutions to improve cleanliness and sanitation. Results indicated that over four months, the program successfully increased community awareness of the importance of responsible waste management. Initial testing found that public knowledge of sustainable waste and settlement management was rated poorly at 46.38%. Attitudes and behaviors scored 49.45% and 48.00% respectively, also falling below acceptable criteria. Final testing revealed significant improvement, with community knowledge in Leato Utara scoring 67.25% for sustainable waste and settlement management, and attitudes and behaviors scoring 73.45% and 70.40% respectively, meeting acceptable standards. In conclusion, the Infrastructure KKN program has positively contributed to improving waste management and sanitation in Leato Village, paving the way for cleaner and healthier settlements.